FluMum: a prospective cohort study of mother–infant pairs assessing the effectiveness of maternal influenza vaccination in prevention of influenza in early infancy. Issue 6 (24th June 2014) - O'Grady, Kerry-Ann F; McHugh, Lisa; Nolan, Terry; Richmond, Peter; Wood, Nicholas; Marshall, Helen S; Lambert, Stephen B; Chatfield, Mark; Andrews, Ross M
Abstract : Introduction: Influenza vaccination in pregnancy is recommended for all women in Australia, particularly those who will be in their second or third trimester during the influenza season. However, there has been no systematic monitoring of influenza vaccine uptake among pregnant women in Australia. Evidence is emerging of benefit to the infant with respect to preventing influenza infection in the first 6 months of life. The FluMum study aims to systematically monitor influenza vaccine uptake during pregnancy in Australia and determine the effectiveness of maternal vaccination in preventing laboratory-confirmed influenza in their offspring up to 6 months of age. Methods and analysis: A prospective cohort study of 10 106 mother–infant pairs recruited between 38 weeks gestation and 55 days postdelivery in six Australian capital cities. Detailed maternal and infant information is collected at enrolment, including influenza illness and vaccination history with a follow-up data collection time point at infant age 6 months. The primary outcome is laboratory-confirmed influenza in the infant. Case ascertainment occurs through searches of Australian notifiable diseases data sets once the infant turns 6 months of age (with parental consent). The primary analysis involves calculating vaccine effectiveness against laboratory-confirmed influenza by comparing the incidence of influenza in infants of vaccinated mothers to the incidence in infants of unvaccinated mothers. Secondary analyses include annual and pooled estimates of the proportion of mothers vaccinated during pregnancy, the effectiveness of maternal vaccination in preventing hospitalisation for acute respiratory illness and modelling to assess the determinants of vaccination. Ethics and dissemination: The study was approved by all institutional Human Research Ethics Committees responsible for participating sites. Study findings will be published in peer review journals and presented at national and international conferences. Trial registration number: The study is registered with the Australia and New Zealand Clinical Trials Registry (ANZCTR) number: 12612000175875.